Parliamentary elections in Jordan: an analytical study of the development of the house of representatives and its impact on the democratic process from 1921 to the present - Al Qudah, Yahya Saleh; Russli Kamarudin,; Nurhidayu Rosli, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study examines the evolution of parliamentary elections in Jordan and evaluates the role of the House of Representatives in the country’s democratic process since the establishment of the Emirate of Transjordan. The study seeks to answer key questions: How has the Jordanian parliamentary system developed over time? What are the main drivers of change? And how has the parliament influenced Jordan’s democratic trajectory? Using a qualitative approach, the research analyzes data from primary and secondary sources, covering the period from 1921 to 2024, divided into five key phases: the Emirate period (1921-1945), the independence period (1946-1967), the martial law period (1967-1988), the political thaw period (1989-2010), and the Arab Spring period (2010-2024). The findings reveal that popular protests and struggles were key drivers of democratic reforms. However, the parliament’s power has remained limited due to executive dominance, frequent dissolutions, electoral laws, and security interventions. Despite regular elections, Jordan continues to be classified as an "authoritarian regime" by the Economist Intelligence Unit’s Democracy Index. The study concludes that Jordan’s political system remains in transition, requiring significant reforms to ensure a fully democratic system with the capacity for peaceful political transitions.